Penguatan Pemolisian Demokratis dalam Perspektif Pendidikan Kewarganegaraan: Sebuah Analisis Konseptual - Mursyid Setiawan; Cecep Darmawan; Muradi Muradi; Syaifullah Syaifullah (Badan Strategi Kebijakan Hukum, 2023)
One effort to strengthen the idea of democratic policing is through civic education. This research has the main aim of analyzing the conceptual aspects contained in civic education in order to provide strengthening ideas for democratic policing. This research also attempts to outline the challenges of democratic policing as viewed from the perspective of civic education in Indonesia. This article uses Gary Goertz's three-level conceptual analysis framework to dissect the conceptual dimensions in civic education that are useful for strengthening democratic policing. Qualitatively, data was obtained using literature studies from various books, journal articles, report documents, and other literature. This study shows that civic education, which is integrated with democracy, politics, law, human rights, anti-corruption, and peace education, can be a vehicle for conceptually strengthening the idea of democratic policing. In addition, this study found a number of challenges for civic education in strengthening democratic policing efforts in Indonesia. The main challenges are the problems that occur in the police institution, including not yet fully supporting democratic culture and spaces for citizens, the issue of police neutrality in political life, the practice of violations of law and human rights by police officers, the existence of corrupt behavior, and the fact that the police has not yet fully become a humanist and non-violent institution. This study requires further research to see to what extent the implementation of the concept of civic education can strengthen democratic policing efforts that are oriented to the citizenship dimension.